Facilitating the Implementation Process of High-Performance Work Systems: The Role of Authentic Leadership - Cao, Man; Zhao, Yixuan; Zhao, Shuming (Frontiers in Psychology, 2020)
Although substantive research has devoted increasing attention to variability in human resource practices at the organization, group, and individual levels, the critical role of line managers’ leadership in predicting this variability in the human resource management delivery and implementation process has been overlooked. Drawing from social information processing theory and HR attributions theory, this study proposes that authentic leadership moderates the positive relationship between department-level high-performance work systems and employee-perceived high-performance work systems. Moreover, employee-perceived high-performance work systems can enhance employees’ thriving at work through commitment-focused HR attributions (well-being and performance). Analyzing the matched data from 145 departments and 834 employees, we found that the extent to which department-level high-performance work systems are positively related to employee-perceived high-performance work systems depends on authentic leadership within departments. We also found that employee-perceived high-performance work systems will result in commitment-focused HR attributions (well-being and performance), which in turn motivate employees to thrive at work. This study sheds light on whether and how line managers’ leadership influences the HRM process.